Charge transport and structure in semimetallic polymers. Issue 1 (16th October 2017) - Rudd, Sam; Franco‐Gonzalez, Juan F.; Kumar Singh, Sandeep; Ullah Khan, Zia; Crispin, Xavier; Andreasen, Jens W.; Zozoulenko, Igor; Evans, Drew
ABSTRACT: Owing to changes in their chemistry and structure, polymers can be fabricated to demonstrate vastly different electrical conductivities over many orders of magnitude. At the high end of conductivity is the class of conducting polymers, which are ideal candidates for many applications in low‐cost electronics. Here, we report the influence of the nature of the doping anion at high doping levels within the semi‐metallic conducting polymer poly(3, 4‐ethylenedioxythiophene) (PEDOT) on its electronic transport properties. Hall effect measurements on a variety of PEDOT samples show that the choice of doping anion can lead to an order of magnitude enhancement in the charge carrier mobility > 3 cm 2 /Vs at conductivities approaching 3000 S/cm under ambient conditions. Grazing Incidence Wide Angle X‐ray Scattering, Density Functional Theory calculations, and Molecular Dynamics simulations indicate that the chosen doping anion modifies the way PEDOT chains stack together. This link between structure and specific anion doping at high doping levels has ramifications for the fabrication of conducting polymer‐based devices. © 2017 The Authors. Journal of Polymer Science Part B: Polymer Physics Published by Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 97–104 Abstract : Employing different anions to dope poly(3, 4‐ethylenedioxythiophene) to very high levels (approaching 50%) results in very different forms of the polymer. The use of nitrate, perchlorate and tosylate yields experimentally determined highly conductive states with anions suggested by simulation to reside within the pi‐pi stacking of the polymer chains. Conversely, chloride and phenylphosphate are not observed in simulation to intercalate within the pi‐pi stacking, which is correlated to reduced electrical conductivity in experiments.